Mediation of Interface Dipoles on SiOx/Si Nanowire Based Inorganic/Organic Hybrid Photodetectors with Enhanced Wavelength‐Selective Sensing Performances - Li, Jheng‐Yi; Wei, Ta‐Cheng; Hsiao, Po‐Hsuan; Wu, Tsung‐Yen; Chen, Chia‐Yun (Advanced materials interfaces, 2023)
The promising hybrid photodetector design is realized through the incorporation of PEDOT:PSS layer with SiOx/Si nanowires (SiNWs), which went beyond the intrinsic limitation of band‐gap associated photosensing characteristics of conventional Si semiconductors toward revolutionarily turning into wavelength‐selective features. These can be interpreted by two determining effects. First, the effective trapping of incident lights with wavelength of 590 nm is evidenced on SiOx/SiNWs. Besides, the creation of interfacial potentials, arising from the positively charged PEDOT:PSS and negatively charged SiOx, manifested the reduction of electron density at PEDOT:PSS surfaces and in turn raised the work function. These features explicitly modulated the carrier‐transport characteristics at hybrid heterojunctions, which accounted for the suppression of photocurrents under light excitations with wavelengths of either 365 nm or 850 nm. The established photodetectors with optimal oxidation treatment resulted in the substantial improvement of both device responsivity and detectivity above 11 times beyond the PEDOT:PSS/SiNWs designs, which shed new light on practical applications of hybrid photodetectors. A new organic/inorganic hybrid strategy that provides the rational design of wavelength‐selective photodetectors is demonstrated.